Deacylcynaropicrin from Cyclolepis genistoides attenuates iron-induced oxidative stress and inflammatory signaling in neuron and glial cells - Alza, Natalia Paola (2025)
Ethnopharmacological relevance: Cyclolepis genistoides has been traditionally used in Argentina, Chile and Paraguay in chronic diseases to intervene pain and inflammation-related conditions, suggesting a strong anti-inflammatory potential, which may also be useful to target neurodegenerative diseases (ND). However, the anti-(neuro)in- flammatory and antioxidant effects of C. genistoides has not been assessed in neurodegeneration models. Aim of the study: To evaluate the antioxidant and anti-inflammatory potential of C. genistoides aqueous extract and its main constituent deacylcynaropicrin (DAC) using neuronal and glial cultures under iron-induced oxidative stress, a common condition in ND. Methods: The metabolite profile of C. genistoides extract was analyzed by UHPLC-DAD-HRMS, and DAC was isolated. The effects of C. genistoides and DAC on iron-induced oxidative stress were assessed using H2DCFDA, NBT, TBARS, and BODIPY581/591 C11 assays, along with NRF2 status. DAC anti-inflammatory activity was evaluated by NO production, and the expression of NFκB, COX-2, IL-1β and GFAP in glial cells. Results: Pretreatment with C. genistoides extract (20 μg/mL) reduced reactive oxygen species and lipid peroxi- dation in iron-treated IMR-32 cells. The extract promoted NRF2 nuclear translocation and upregulated GCLc and catalase. DAC exhibited similar antioxidant effects. Furthermore, DAC (10 μM) demonstrated anti-inflammatory activity by inhibiting NO production, NFκB nuclear localization, and COX-2 and IL-1β expression in macrophages and glial cells, and it reduced reactivity and lipid peroxidation in astrocytes. Conclusions: Our work shows for the first time that C. genistoides and DAC display pronounced antioxidant and anti-inflammatory effects in cellular ND models, corroborating the scientific basis of the traditional use